Estudo experimental do equilíbrio de fases de hidratos de dióxido de carbono na presença de inibidores termodinâmicos - Guembaroski, Amanda Zorzi (2016)
Gas hydrates are crystalline compounds formed by hydrogen-bonded water frameworks. Hydrates are stabilized by non-polar molecules of low molecular diameters (guest molecules), which are occluded in cavities (host lattice) of the crystalline structure formed by water molecules. The interaction between the host and guest molecules occurs by van der Waals forces. The formation of gas hydrates depends on temperature, pressure and gas composition. In the oil and gas industry, the occurrence of hydrates can cause problems in pipelines, damage to equipments, production interruption or impairment and operational safety issues. Therefore, the knowledge of the conditions under which hydrates occur is of extreme importance to that industry. This study intends to investigate the hydrate phase equilibrium curves for systems of carbon dioxide + inhibitors aqueous solutions, in order to establish the strength of hydrate inhibition at different inhibitor mass concentrations (ethanol: 5%, 10% e 15% and sodium chloride: 5%, 10% e 15%). The experimental temperature ranged from 272.15 to 281.65 K for pressures up 52.4 bar. Experimental measurements were made to obtain hydrate equilibrium curves (P vs T curves) by means of the synthetic static method using an isothermal procedure. The phase equilibrium apparatus was built in the NUEM/UTFPR lab. Literature data were selected and compared with the results obtained in this work. From the phase equilibrium data, the enthalpy of dissociation for these hydrates were estimated by applying the Clausius–Clapeyron equation. In addition, the experimental data are compared to prediction tools (CSMGem and Multiflash®) and the absolute average deviation between the measured and predicted data are reported. It was observed that the sodium chloride provides the strongest inhibition on the LH2O-H-V phase equilibrium when compared to ethanol.